Peranbadan Pembinaan Qari-Qariah, Hafiz-Hafizah Dan Seni Kaligrafi Al Qur’an (BAPQAH SIKA) Medan Dalam Meningkatkan Kualitas Bacaan Al Qur’an Peserta Kelas Dasar - Farhan Indra; Irfan Mansyur; Mahyuni Mahyuni; Mulia Ramadhani; Najamuddin Najamuddin; Muhammad Al Farizi; Rio Hanai Ritonga; Helmi Yahya Hutasuhut (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
A coaching institution known as Badan Pembinaan Qari-Qariah, Hafiz-Hafizah Dan Seni Kaligrafi Al Qur'an (BAPQAH SIKA) Medan offers a program that focuses on the study of the Qur'an, from the art of reading it to its contents (Tafsir Al Qur'an). The purpose of this additional study was to determine the role that BAPQAH SIKA Medan plays in enhancing the reading proficiency of elementary class participants. Different kinds of field research and descriptive qualitative methods are used in this study. According to the findings of this study, BAPQAH SIKA Medan provides intensive training by distinguishing the abilities of students in each class Keywords: Upgrade, quality, BAPQAH SIKA Medan